The Brazilian 'Blue Amazon' Program: A New Chapter for Submarines Nuclear-Powered International Domain? - Almeida, Laisa Branco Coelho C. de; Zavanella, Emanuele Mario (Revista Tribuna Internacional, 2020)
This paper seeks to analyze the currently existing international rules governing the usage of nuclear-powered submarines and its application towards the Brazilian program announced in 2018 of a national fleet investment in nuclear technology to strategically defend its coastline, ‘the blue amazon’, bringing the world's attention to the nuclear development by new global State actors and a non-permanent member of the United Nations Security Council. This paper examines the project's (in) compatibility to vital international legally documents rests in the discussion, mainly, the Model Additional Protocol of the International Atomic Energy Agency (IAEA) - safeguards agreements - still not ratified by the Brazilian government and regional conventions align with South State’s, e.g. Argentina, which restricts nuclear technology usage by other member States. Conversely, how the international law intents to respect Brazil’s sovereignty rights to invest in military ships, meanwhile impose coercive measures to indirectly exercise any regulation powers towards the nuclear activity being performed by its safeguards program. It concludes by highlighting the exception of nuclear material for nuclear fuel purposes to safeguard in Treaty on the Prohibition of Nuclear Weapons (NPT), and the importance of the ambitious project to contribute to the country's and South America's scientific and technological development.